AMOR FATI: LOVE THYSELF BY BECOMING WHAT YOU ARE! NIETZSCHE ON THE FREEDOM OF THE WILL - Mihai NOVAC (Challenges of the Knowledge Society)
Nietzsche’s distinction between the master and the slave moralities is certainly one of his most notoriously famous moral and political notions. To claim that there are two main perspectives on the world, one belonging to the accomplished, the other to the unaccomplished side of humanity and, moreover, that the last two millennia of European alleged cultural progress constitute, in fact, nothing more than the history of the progressive permeation of our entire Weltanschauung, of our very values, thoughts and feelings by the so called slave morality, while all the more finding the virtue of this process in a future self-demise of this entire decadent cultural and human strain, is something that has shocked and enraged most of the ideological philosophers ever since. As such, at a certain moment, despite their substantial doctrinaire differences, almost everybody in the ideologized philosophical world, would agree on hating Nietzsche: he was hated by the Christians, for claiming that “God is dead”, by the socialists for treating their view as herd or slave mentality and denying the alleged progressively rational structure of the world, by the liberals much on the same accounts, by the ‘right wingers’ for his explicit anti-nationalism, by the anarchists for his ontological anti-individualism (i.e. dividualism), by the collectivists for his mockery of any gregarious existence, by the capitalists for his contempt for money and the mercantile worldview, by the positivists for his late mistrust in science and explicit illusionism (i.e. the notion that illusions are a necessary fact of life). However, being equally resented by all sides of the political, moral, theological and epistemic spectra might indicate that one is, if not right, or unbiased, at least originally and personally biased. Any view that coherently achieves such form of specific equal contestation, especially one that has so robustly continued to do so for more than a century, deserves some consideration.